The commodification of the criminal corpse: 'selective memory' in posthumous representations of criminal. (2nd July 2016) - Denham, Jack
Abstract: For the last 20 years, you have been able to buy body parts of criminals on the Internet. Through repeated exposure to the corpse in popular culture, the boundaries between real and facsimile are blurring when it comes to the cadaver, but 'murderabilia', a consumeristic arm of 'dark tourism', is often sold as the most authentic way to consume crime in the culture industry. Foltyn argues that in the process of consuming death, we are 'creating corpse facts and fictions'. With regards to murderabilia, my contribution offers the concept of 'selective memory' as a way to understand how positive histories are enhanced in posthumous representations of criminal. A 'selective memory' augments these corpse fictions, more than the facts, making for lopsided representations of the criminal corpse. This paper of three parts analyses historical commodification of the criminal corpse, arguing that being dead has often been a prerequisite of achieving notoriety for criminals. Second, a case study of Charles Manson is used to showcase the brand-like qualities attached to successful criminal celebrities. Third, this case study is continued through news media representations, to show that the criminal corpse is recalled with a 'selective memory', missing violent aspects and focussing instead on brand.